Mitochondrial DNA copy number of leucocytes as ageing marker and risk factors for age-related diseases in human. - Maximov, V N; Malyutina, S K; Orlov, P S; Ivanoschuk, D E; Mikhailova, S V; Shapkina, M Y; Hubacek, J; Holmes, M; Bobak, M; Voevoda, M I (Advances in gerontology, 2019)
We used quantitative real-time PCR method to analyse mtDNA copy number in a random subsample (n=996; 358 men aged 66,31±7,24 years; 468 women aged 67,62±7,1 years) selected from a population cohort (n=9 630) examined at baseline in international project HAPIEE in Novosibirsk, Russia, in 2003-2005. The participants were re-examined after 12 years in 2015-2017. The average relative number of mtDNA copies in peripheral blood leukocytes was greater in women than in men, independently of age and smoking (p=0,001). mtDNA copy number was inversely correlated with age both in men (p=0,005) and women (p<0,001). In age adjusted analysis, mtDNA copy number was inversely associated with waist, hip and heart rate in both sexes. In addition, mtDNA copy number in women was inversely associated with triglycerides and glucose, aterogenity index and positively with HDL cholesterol. In men, mtDNA copy number was positively associated with physical activity. The age-adjusted mean of mtDNA copy number among male never-smokers was greater than in smokers (p=0,003), and the mean mtDNA copy number was lower in women with diabetes than in women without diabetes (p=0,005). In both sexes, subjects with baseline history of hypertension had lower mtDNA copy number after 12-year follow-up than those without hypertension (p=0,05). This broadly supports the hypothesis that mtDNA copy number may act as biomarker of ageing.
Keywords: senioři; Russia; Aging; risk factors; Leukocytes; Diagnosis; diabetes mellitus; hypertension; sexuální faktory; Rusko; Middle Aged; DNA Copy Number Variations; mužské pohlaví; DNA, Mitochondrial; population; mtDNA copy number; ischemic heart disease; stárnutí; diagnóza; ženské pohlaví; ageing biomarker; Humans; mitochondriální DNA; biologické markery; Sex Factors; lidé středního věku; genetics of longevity; rizikové faktory; Biomarkers; age-dependent diseases; variabilita počtu kopií segmentů DNA; Aged; leukocyty; Female; Risk Factors; lidé; Male